Mediastinal and retroperitoneal transdiaphragmatic bronchogenic cyst with gastric mucosa - Rahaf Ibrahim; Sawssan Ali; Bassam Darwish (Elsevier, 2021)
Background: Congenital cystic lung lesions are rare lung malformations. They are mostly diagnosed by a routine antenatal ultrasound scanning. Clinical symptoms ranging from asymptomatic condition to life-threatening course. Case and outcomes: We presented a case of congenital cystic lung malformation, the case demonstrated a 20- month- old boy who was reported to our hospital because he was diagnosed prenatally with a right-sided cystic lung mass. He was asymptomatic. A diagnosis of mediastinal retroperitoneal bronchogenic cyst was made radiologically. He underwent a successful right thoracotomy and the transdiaphragmatic cystic mass was completely resected. Histologic examination revealed bronchogenic cyst with gastric mucosa. Conclusion: Early diagnosis improves outcomes in infants with congenital cystic lung anomalies. Surgical management is the treatment of choice for congenital cystic lung malformations.